Social perceptions of physical education and sports classes in the cultural imagination of high school students exempt from sports participation - Toufik, Amara; Yazid, Amoura (The International tax journal, 2025)
This study aims to uncover the social and cultural perceptions of physical education and sports classes among exempt high school students. The researchers employed a descriptive-analytical approach with a random sample of 200 exempt students from four high schools in Boumerdès Province. A questionnaire was used to collect data. The results obtained by the researchers highlighted the following: - Religious justifications exist for exemptions related to gender mixing and clothing; - Physical education is perceived more negatively than other subjects; - Health-related justifications, such as chronic illnesses or disabilities, were common. In conclusion, this study offers several recommendations, including the enactment of a law that would require school health physicians to provide accurate diagnoses of students’ health conditions, along with comprehensive and convincing medical files, rather than leaving it to personal considerations alone.